Strange loves: a remarkable case of aberrant copulation in beetles (Coleoptera: Meloidae, Chrysomelidae) - Di Giulio, Andrea; Gisondi, Silvia; Molfini, Marco; Riccieri, Alessandra; Scarparo, Giulia; Bologna, Marco Alberto (Fragmenta entomologica, 2017)
A case of copulation between two mimic and repellent beetle species (a male of Timarcha fracassii, and a female of Meloe autumnalis), belonging to distinct families (Chrysomelidae, Meloidae), is recorded.